Efficacy of Calcium Lactate in Reducing Browning of Fresh-Cut Organic Thai Eggplant cv. Chao Phraya - Krongyut, Wiraya; Kingwatee, Niras; Shaban, Nidal Tabit (AGRIVITA Journal of Agricultural Science, 2024)
Browning limits the shelf life of fresh-cut eggplant. To control browning, organic Thai eggplant cv Chao Phraya is treated with calcium lactate at different concentrations (0.5, 1.0, 1.5 and 2.0%) a 5 minutes dip before storage at 10°C with 90% relative humidity for 4 days. Water dip and no dip serve as control treatments. Calcium lactate at 0.5-1.0% remarkably reduces browning to a moderate degree; in contrast, higher calcium lactate concentrations, water dip and no dip treatments caused very severe browning at the end of storage. Browning severity is also manifested as reduced lightness (L*) values and increased brown pigment concentration. The total phenolic content did not change much in response to the 0.5-1.0% calcium lactate treatment, while the other treatments reduced the phenolic content, indicating conversion to brown pigments. Polyphenol oxidase (PPO), phenylalanine ammonia lyase (PAL) and peroxidase (POD) were significantly lower with 0.5-1.0% calcium lactate than with other treatments. This supported the reduction of browning by these treatments.